Quantum mathematics: backgrounds and some applications to nonlinear dynamical systems - Bogolubov, N.N.; Golenia, J.; Prykarpatsky, A.K.; Taneri, U. (Нелінійні коливання, 2008)
Backgrounds of a new mathematical physics discipline ’Quantum Mathematics’ are discussed and analyzed
from both historical and analytical points of view. The magic properties of the second quantization method,
invented by V. Fock in 1934, are demonstrated, and an impressive application to the nonlinear dynamical
systems theory is considered. Обговорюються витоки нової дисциплiни в математичнiй фiзицi — квантової математики
— як з iсторичної, так i з аналiтичної точок зору. Проiлюстровано дивовижнi властивостi
методу вторинного квантування, який був запропонований Фоком у 1934 р., та розглянуто
вражаючi застосування до теорiї нелiнiйних динамiчних систем.